Contributing factors for low consumption of animal food among children aged 6-23 months in alive and thrive intervention areas of Bangladesh - Mukta, Umme Salma; Chakraborty, Barnali; Sayka, Umme; Haque, Md. Raisul; Mia, Md. Moslem Uddin (BRAC Research and Evaluation Division (RED), 2019)
Introduction: In Bangladesh about two-thirds of total food consumption is rice as main staple food, especially for the poor, in addition to some vegetables, pulses and small quantities of fish, meat, egg, etc. if and when available. The similar dietary pattern and practices were found for under-two children in the intervention areas of Alive and Thrive (A& T) project where mothers were counseled on appropriate complementary feeding practice as a component of Infant and Young Child Feeding (IYCF). BRAG-RED intended to explore these issues to recognize the gaps that might be addressed to increase the consumption of protein from animal foods among the children through the IYCF interventions in A& T areas. Objective: This study aims to identify the barriers leading to low consumption of animal foods by children aged 6-23 months in A & T intervention areas; and to assess their knowledge and practices of dietary intake through 24-hour recall. Methods: Mixed methods were chosen to find comprehensive information in 12 upazi/as, 3 from each of Barguna, Sylhet, Chittagong and Dinajpur districts. The Pusti Kormi (PK), Shasthya Shebika (SS), and mothers/caregivers enrolled in the A& T intervention areas were selected for interview; and those who had involvement in providing the services. In addition, other programme staff from the supervisory level who involved in providing services was also interviewed. Findings: The study revealed from the quantitative findings that, in intervention areas intake from animal sources was 7 -12g at 1 years and 18g at 2 years where the recommended dietary average (RDA) was 14g for less than one years and 16g for less than 2 years. On the other hand in control areas at both age groups the intake ratio was lower. From the qualitative findings majors contributing factors for feeding from animal sources was, lack of knowledge, lack of awareness on protein deficiency, barriers from the family members, myth, etc. Almost similar barriers was found from the quantitative findings like; financial crisis (80.3%), mothers lack of knowledge and awareness (67%), unavailability of the products in near local market (5%), etc. Conclusion: Food consumption from animal sources might be increased among less than two years children by reducing those barriers, by strengthening efforts in the awareness development process in creating demand for appropriate IYCF services at household level especially intake foods from animal sources to improve children's nutritional status.